Markets Minding with Crowd Social Behavior: Emotional Control Sharing Trading Mob Psychology - Styliadou, Artemis A.; Williamson, Simona P. (New Horizons in Education and Social Studies Vol. 9, 2021)
Trading psychology refers to traders’ functionalities and mindset during their time on the markets. It should determine the extent and the limits to which they succeed in securing a profit or it can provide an explanation as to why a trader incurred heavy losses. Traders well-versed in trading psychology will generally not act on bias or emotion. Hence, a real-world problem in stock markets is always the emotional control. Obviously, the real question is how to “control” the bad emotions and feelings (e.g. fear and greed), just before the execution orders, rather than to “eliminate” them. In order to address the emotional control problem, this article introduces the innovative concept “Emotional Control Sharing Trading Psychology, ECSTP”, which has been defined as a collaborative trading engineering term. Then, an empirically-tested approach (statistical analysis) is performed in order to initially evaluate the proposed term in real- world NYSE trading strategies as far as the returns are concern. The evaluation result shows an up to 29% improve in returns after the adoption of the proposed term. The implications of the proposed trading approach are pointed to better and more stable decisions with the cost of groupware coordination and communication problems. Always, a well designed and organized collaborative intervention improves groupware efficiency and effectiveness for investment decisions.